Le tracé extravagant des cartes dans Moby-Dick et Walden - Michel Imbert; Julien Nègre (Transatlantica)
This article is focused on mapping in Moby-Dick (1851) and Walden (1854). Michel Imbert comments more specifically on the chapters of Melville’s novel explicitly devoted to maps: both the map of Nantucket and the charts used by Captain Ahab to set his course are telltale signs of the will to plot an empire even as they blot out the abyss within. Insanity looms large through the blanks. In the second part, Julien Nègre focuses on the role played by maps and surveying in Walden, starting with the map of Walden Pond included by Thoreau in his text. Beyond its topographical dimension, surveying becomes for Thoreau a means of revealing what the eye cannot detect in the world – although in the end, paradoxically, it moves toward a gradual erasure of maps and landmarks.